JAPANESE APOLOGY EXPRESSIONS BY JAVANESE AND SUNDANESE SPEAKERS - Azizia Freda Savana; Wistri Meisa (Universitas Islam Sumatera Utara (UISU), 2021)
This research discusses expressions of apology in Japanese by Javanese and Sundanese speakers at Universitas Muhammadiyah Yogyakarta. The apology differs between Japanese and Indonesian. Apologizing to the Japanese uses many reasons, the Japanese may distrust the speech partner and cause misunderstanding. In learning Japanese, Javanese-speaking learners are different from Sundanese-speaking learners because their culture also influences them. This research aims to determine the strategy of apology expression by Japanese language learners who speak Javanese and Sundanese as seen from the semantic formula and the differences between the two. This research used a descriptive method with a qualitative approach to describe the strategy of apologizing in Japanese by Javanese and Sundanese mother tongue learners using semantic formulas. Respondents were UMY students from level 2 and level 3 PBJ Study Program with 15 Javanese speaking students and 15 Sundanese speaking students. This research showed that most Japanese learners who speak Javanese and Sundanese tended to use the Speech Act Indication Expression (apology and appreciation) when expressing Japanese apologies. They used polite language ultimately when apologizing to lecturers.